2001
DOI: 10.1007/s004390100561
|View full text |Cite
|
Sign up to set email alerts
|

Association between nasal allergy and a coding variant of the Fc ε RI β gene Glu237Gly in a Japanese population

Abstract: The gene for the beta-chain of the high-affinity receptor for IgE (Fc epsilon RI beta) has been proposed as a candidate gene for atopy. A coding variant Glu237Gly has been studied in various populations with asthma and atopy, and the results were controversial for association of the variant with atopy/asthma. Because nasal allergy is a more common atopic disease and shows less remission than asthma, we analyzed whether the Glu237Gly variant is correlated with nasal allergy. The study enrolled 233 patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
28
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 39 publications
2
28
0
Order By: Relevance
“…The SNP in exon 7 of human Fc⑀RI␤, which results in the Glu237Gly polymorphism, has been implicated in atopic diseases as a predisposing genetic factor (3,4,6,7). In the present study, we found significant association between the Glu237Gly polymorphism and the expression level of Fc⑀RI on blood basophils (Fig.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…The SNP in exon 7 of human Fc⑀RI␤, which results in the Glu237Gly polymorphism, has been implicated in atopic diseases as a predisposing genetic factor (3,4,6,7). In the present study, we found significant association between the Glu237Gly polymorphism and the expression level of Fc⑀RI on blood basophils (Fig.…”
Section: Discussionsupporting
confidence: 67%
“…Further studies have shown that two SNPs in exon 6 are often absent in certain populations, including the Japanese, whereas another SNP in exon 7, which causes an amino acid substitution, Glu237Gly, is more common (4,5). Although some reports have presented positive association between the Glu237Gly polymorphism and atopic diseases (3,4,6,7), other reports have not (8,9). In contrast, it has also been demonstrated that the amino acid variations in the ␤-chain, including the Glu237Gly mutation, does not affect the expression or function of Fc⑀RI in vitro (10,11).…”
mentioning
confidence: 99%
“…The study of SNPs of FcεRIβ and IFNGR2 mainly focused on their relationships with allergic diseases such as asthma (Kim and Park, 2006;Sanak et al, 2007) and allergic rhinitis (Nagata et al, 2001), and was used to treat malignant tumors such as non-Hodgkin lymphoma (Purdue et al, 2007;Chen et al, 2011) and gastric cancer (Hou et al, 2007). IFNGR1 was reported to correlate with β-lactam allergy, however, the relationship between SNP of IFNGR2 and β-lactam allergy was not clear.…”
Section: Relationship Between β-Lactam Allergy and Other Genetic Polymentioning
confidence: 99%
“…1 Its main characteristics are defined as sneezing, rhinorrhea, nasal stuffiness and nasal itching and may be involved in an imbalance in the Th1/Th2 immune response. 2,3 Although the exact pathogenetic mechanisms of AR are still unknown, there is ample evidence suggesting that AR is a complex multifactorial disorder including both genetic and environmental factors [4][5][6][7][8] and some low-penetrant genes have been identified as potential AR susceptibility genes. [9][10][11] Among them, an important one is angiotensin converting enzyme (ACE), which contains 26 exons and 25 introns and is located on chromosome 17q23.…”
Section: Introductionmentioning
confidence: 99%